Growth Hormone Supplementation and Psychosocial Functioning to Adult Height in Turner Syndrome: A Questionnaire Study of Participants in the Canadian Randomized Trial - Rovet, Joanne F.; Van Vliet, Guy (Frontiers in Endocrinology, 2019)
Despite the long-held belief that growth hormone supplementation provides psychosocial benefits to girls with Turner syndrome (TS), this assumption has never been rigorously tested in a randomized control trial. As a sub-study of the Canadian growth-hormone trial, 70 girls with TS who received injections (GH group) and 61 similarly followed untreated controls (C) were evaluated for multiple facets of psychosocial functioning using standardized questionnaires completed by parents and patients. Test packets were distributed (i) at baseline (session 1, mean age = 10.4 y), (ii) before estrogen therapy for puberty induction (session 2, mean age = 13.0 y), (iii) after one year of estrogen therapy (session 3, mean age = 14.4 y), and (iv) when growth stopped (session 4, mean age = 16.3 y). Groups were compared for four domains of psychosocial functioning: social, behavioral, self-esteem, and academic. Results were also correlated with indices of adult height. No group global differences were observed on any scales or subscales from the four psychosocial domains. GH and C both showed age-related improvements in social problems, externalizing behavior problems, and school functioning, whereas their social competence and social relations declined with age. Parents and patients claimed GH was teased less than C but that C had more friends than GH. Tt the early sessions, GH outscored C in perceived popularity, social engagement, and behavioral adaptation as well as self-esteem, whereas parents reported C was less anxious, depressed, and withdrawn than GH at adult height. Correlational analyses revealed that for GH, adult height and height gain were both correlated with multiple parent- and/or self-reported indices in all four psychosocial domains while for C, adult height was correlated only with total self-concept and school functioning. The observed modest gains in psychosocial functioning for patients with TS treated with GH highlight the need for alternative approaches to assist them in coping with the challenges of their condition.